Iranian Senior High School EFL Teachers' Perspectives of Lesson Study: Perceiving Challenges, Hindrances, and Benefits - Nayereh Behdad; Mohammad Hassan Tahririan (Journal of Modern Research in English Language Studies)
Today, Lesson Study (LS) is a prerequisite to the professional development of teachers in high school settings. The present study aims to figure out how Iranian language teachers' attitudes towards LS can motivate their engagement or denial to join LS projects. The study is also driven by the desire to discover the obstacles to achieving LS from the perspective of language teachers in Iran. A research design on explanatory sequential mixed methods was used. The instruments used to collect the data consisted of questionnaires at the quantitative stage along with language teachers' reflection notes and semi-structured interviews during the qualitative phase of the study. A total of 206 senior high school language teachers participated in the first phase of the study, of which 14 participated in the interview and 20 wrote reflection notes for the second phase of the research. The instrument used to analyze the data in the quantitative phase was SPSS software and, at the qualitative step, MAXQDA software. The end result of both quantitative and qualitative findings draws attention to the importance of mentoring high school EFL teachers to be able to complete LS and puts emphasis on the beneficial role of Lesson Study. These findings can have implications for EFL teachers, school officials, EFL teacher educators, curriculum designers, and policymakers to pave the way for attaching importance to LS as a teachers' development approach. In terms of the limitations of this study, follow-up studies can mitigate the limitations of this research by replicating it using a larger sample of teachers teaching different levels of students in different classes for a much longer duration.